How Well Can Multivariate and Univariate GWAS Distinguish Between True and Spurious Pleiotropy? - Fernandes, Samuel B.; Zhang, Kevin S.; Jamann, Tiffany M.; Lipka, Alexander E. (Frontiers in Genetics, 2021)
Quantification of the simultaneous contributions of loci to multiple traits, a phenomenon called pleiotropy, is facilitated by the increased availability of high-throughput genotypic and phenotypic data. To understand the prevalence and nature of pleiotropy, the ability of multivariate and univariate genome-wide association study (GWAS) models to distinguish between pleiotropic and non-pleiotropic loci in linkage disequilibrium (LD) first need to be evaluated. Therefore, we used publicly available maize and soybean genotypic data to simulate multiple pairs of traits that were either i) controlled by quantitative trait nucleotides (QTNs) on separate chromosomes, ii) controlled by QTNs in various degrees of LD with each other, or iii) controlled by a single pleiotropic QTN. In addition to confirming that multivariate GWAS was either equal to or more powerful than univariate GWAS, we also showed that multivariate GWAS could not distinguish between QTNs in LD and a single pleiotropic QTN. In contrast, a unique QTN detection rate pattern was observed whenever the simulated QTNs were in high LD or pleiotropic. Collectively, these results suggest that multivariate and univariate GWAS should both be used to infer whether or not causal mutations underlying peak GWAS associations are pleiotropic. Therefore, we recommend that future studies use a combination of multivariate and univariate GWAS models, as both models could be useful for identifying and narrowing down candidate loci with potential pleiotropic effects for downstream biological experiments.